The effect of an anonymous grading reform for male and female university students - Joakim Jansson; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2024)
This paper presents evidence that anonymous grading benefits female university students, based on a university-wide reform. Female grades improve by 0.04-0.06 standard deviations relative to males, with the effect strongest in smaller classes and male-dominated departments.
Keywords: I23; J16; 330; Anonymous grading; gender differences; Grading bias; University